2006
DOI: 10.1373/clinchem.2005.058396
|View full text |Cite
|
Sign up to set email alerts
|

Immunoassays Developed for Pregnancy-Associated Plasma Protein-A (PAPP-A) in Pregnancy May Not Recognize PAPP-A in Acute Coronary Syndromes

Abstract: Background: Pregnancy-associated plasma protein-A (PAPP-A) concentrations are increased in the circulation of patients with acute coronary syndromes (ACS) and are associated with future adverse cardiac events. PAPP-A in ACS differs from PAPP-A in pregnancy in that PAPP-A in ACS is not complexed with the proform of eosinophil major basic protein (proMBP). We investigated the effect of antibody selection on the utility of PAPP-A assays for measurement of PAPP-A in pregnancy and/or ACS, and whether immunoassays f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 30 publications
2
11
1
1
Order By: Relevance
“…The absolute PAPP-A serum concentrations obtained in our study sample may, therefore, not be directly comparable with the PAPP-A concentrations reported by other authors (10,15,18,31,32) because of the different methods used for PAPP-A measurement. It is well known that atherosclerosis-related PAPP-A differs from pregnancy-related PAPP-A, since the first circulates as a homodimeric active form, uncomplexed with the proform of the eosinophil major basic protein (proMBP).…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…The absolute PAPP-A serum concentrations obtained in our study sample may, therefore, not be directly comparable with the PAPP-A concentrations reported by other authors (10,15,18,31,32) because of the different methods used for PAPP-A measurement. It is well known that atherosclerosis-related PAPP-A differs from pregnancy-related PAPP-A, since the first circulates as a homodimeric active form, uncomplexed with the proform of the eosinophil major basic protein (proMBP).…”
Section: Discussioncontrasting
confidence: 89%
“…It is well known that atherosclerosis-related PAPP-A differs from pregnancy-related PAPP-A, since the first circulates as a homodimeric active form, uncomplexed with the proform of the eosinophil major basic protein (proMBP). Immunoassays used to detect total PAPP-A may not be accurate (32). Thus, we used an ultrasensitive PAPP-A ELISA developed for measuring PAPP-A molecules but not the proMBP subunit to avoid false positive results.…”
Section: Discussionmentioning
confidence: 99%
“…We tested the performance of the DRG ELISA with 4 ACS serum samples (from 4 AMI patients) that contained high concentrations of PAPP-A (19.2 mIU/L, 22.8 mIU/L, 49.4 mIU/L, and 145.0 mIU/L, respectively) measured with our total PAPP-A assay, and we found that only the sample that had a PAPP-A concentration of 145.0 mIU/L was actually measurable with the DRG ELISA. Thus, the negative study results obtained by Dominguez-Rodriguez et al are quite understandable and highlight the importance of the selection of proper immunoassays for PAPP-A measurement in the ACS samples, as we previously pointed out (23 ).…”
Section: Discussionmentioning
confidence: 74%
“…[215][216][217] Different assays may therefore perform differently. 218 It has been shown that free PAPP-A is a better predictor than total PAPP-A.…”
Section: Pregnancy-associated Plasma Protein Amentioning
confidence: 99%